2012
DOI: 10.1183/09031936.00196311
|View full text |Cite
|
Sign up to set email alerts
|

TLR9- and Src-dependent expression of Krueppel-like factor 4 controls interleukin-10 expression in pneumonia

Abstract: The release of potent pro-inflammatory mediators is crucial to mounting an efficient host response during infection. However, excessive inflammation may lead to deleterious tissue damage. This is highlighted in severe pneumococcal pneumonia, in which the delicate balance between a robust inflammatory response necessary to kill pneumococci and the loss of organ function determines the outcome of the disease.We assessed the regulation of the potent anti-inflammatory cytokine interleukin (IL)-10 in pneumococcal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…45 Studies have shown that KLF4 has a role in mediating proinflammatory signaling in macrophages, 46,47 and it regulates anti-inflammatory cytokines such as interleukin-10. 48 Chronic lung inflammation has been associated with tumorigenesis in the lung. As one of the most common genetic changes in lung cancer, K-ras activation induces a robust inflammatory response.…”
mentioning
confidence: 99%
“…45 Studies have shown that KLF4 has a role in mediating proinflammatory signaling in macrophages, 46,47 and it regulates anti-inflammatory cytokines such as interleukin-10. 48 Chronic lung inflammation has been associated with tumorigenesis in the lung. As one of the most common genetic changes in lung cancer, K-ras activation induces a robust inflammatory response.…”
mentioning
confidence: 99%
“…These studies provide convincing evidence that may reinforce the therapeutic interest for IFN administration in targeted groups of patients with IPF. (Table 1) TLR9 is an endosomal receptor that senses unmethylated CpG nucleotides commonly found in bacterial and viral DNA genomes and once bound to its ligands leads to activation of the MyD88 canonical pathway and the induction of JNK kinase and NF-kB expression (Platz et al, 2004;Zahlten et al, 2013). On the contrary to TLR2 and TLR4, TLR9 endogenous expression in the normal airway epithelium is relatively low and its actions are mainly mediated by adaptive immune cells such as plasmacytoid dendritic and B-cells (Platz et al, 2004).…”
Section: Intracellular Toll-like Receptorsmentioning
confidence: 97%
“…The production of IL-10 has been reported to be dependent on the NF-ÎșB pathway regulation by TLRs and NLRs. Given its anti-inflammatory nature, it reduces the INTRODUCTION inflammation by inhibiting production of TNF-α, IL-1ÎČ, IL-6, and IL-8 in mononuclear phagocytes 120,134,135,136 .…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%